Strengthening archival culture for the conservation of documentary heritage in public companies in the Metropolitan Area of Pereira - Mejía Medina , Olga Liliana
This article arises as a product of the research project that was formulated and executed in 2022, with apprentices and instructors from the Technologist training program in Document Management of SENA, Regional Center of Commerce and Services; with the objective of investigating and knowing the current situation of some public and private companies with public functions, especially in everything related to compliance with the document management regulations of the General Archive of the Nation of Colombia and the application of the different archival instruments . In this process, a qualitative methodology was applied and various information gathering techniques were used, such as: semi-structured interviews, visits to companies and, finally, a Technological Dissemination Event was held to strengthen and sensitize the attendees sent from the different companies and general public, about the importance of ensuring adequate document management in entities. The result of this work reflects the lack of archival awareness in this Region, taking into account that of 74 companies to which the interview was applied, very few have an archival culture. The awareness training was attended by 230 people connected through the Meet platform and 100 people in person. Certifying 282 people.